2013
DOI: 10.1016/j.apsusc.2012.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen behaviour in amorphous Si/Ge nano-structures after annealing

Abstract: The relationship between blistering, H content and de-passivation of the dangling bonds has been studied in annealed hydrogenated a-Si/a-Ge superlattice (SL) nanostructures grown by RF sputtering. Measurements have been carried out by ERDA, IR absorbance and AFM. By comparison with parallel investigations on a-Si and a-Ge single layers it has been established that the bubbles causing blistering in the annealed SLs very likely start to grow in the Ge layers of the SL because H is released from Ge much earlier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…They have developed from nano-and micro-sized voids, decorated by SiH 2 dihydrides and associated chains, which have increased their volume because of the increase of the inside pressure due to the thermal expansion of the H 2 gas upon annealing. The inside blister pressure was calculated to be on the order of 50 MPa (Frigeri et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have developed from nano-and micro-sized voids, decorated by SiH 2 dihydrides and associated chains, which have increased their volume because of the increase of the inside pressure due to the thermal expansion of the H 2 gas upon annealing. The inside blister pressure was calculated to be on the order of 50 MPa (Frigeri et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Here we address in detail this issue. In a previous work (Frigeri et al, 2013) there was evidence of the formation of bubbles and surface blisters in hydrogenated a-Si/a-Ge multilayers and a-Si layers upon annealing which suggested there could be some relationship between those structural features and the behavior of H as a function of annealing. On the other hand, in the literature several papers suggested the presence of molecular H in voids embedded in a-Si:H (Acco et al, 1996;Beyer, 2003;Chabal and Patel, 1987;Jackson and Tsai, 1992;Street, 1991;Manfredotti et al, 1994).…”
Section: Introductionmentioning
confidence: 95%
“…The degradation of the surface quality of several types of material is often due to the formation of blisters [1][2][3][4][5][6]. Blistering is caused by voids inside the material which have reached a sufficient size to touch and deform the surface because of the increased pressure of some gas inside the voids [1][2][3][4][5][6][7][8]. In the worst cases blisters burst leaving craters [1,6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of our group on a-Si:H layers submitted to annealing it was found that the cause of the structural degradation of the layers in the shape of blisters and craters was the change of the hydrogen bonding configuration [17][18][19][20]. In this paper we investigate whether this also occurs in a-Ge:H by submitting as-deposited films with different H content to annealing.…”
mentioning
confidence: 96%
“…Even much less literature exists about blisters/craters in the case of not-implanted hydrogenated a-Ge [20,21].…”
mentioning
confidence: 99%